Absolute length of urban and rural Spanish vowels of the Ñuble province - Pereira, Daniel Ignacio; Soto Barba, Jaime (Boletín de Filología, 2011)
The present work compares the absolute length of three groups of speakers of Spanish of the Ñuble province (Chile): urban upper middle class, urban lower class and rural lower class. The acoustic data shows a relationship between social status and vowels length. The closer to the urban centre and the higher the social class of the speakers the shorter their vowels and vice versa. The facts that can explain this phenomenon are related to more or less articulatory tension. However, it is also related to extra linguistic aspects such as the conception of time of the subjects, as well as the degree of familiarity with the communicative situation of the sample recording process.